The Moderating Role of Liquidity in the Relationship between Leverage, Firm Size, and Profitability - Inrawan, Ady; Sembiring, Lenny Dermawan; Loist, Christine (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the role of liquidity in moderating the effect of capital structure and firm size on profitability. The data used in this research is secondary data from companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The study employs panel data with a sample of 45 companies selected using purposive sampling, resulting in 225 observations. The analysis uses panel data regression with EViews 13 software, with the best model chosen through the Chow, Hausman, and Lagrange Multiplier tests. The study results indicate that capital structure and liquidity do not significantly affect profitability, while firm size positively affects profitability. Furthermore, liquidity does not moderate the effect of capital structure and firm size on profitability. These findings provide implications for companies and investors in designing strategies and making decisions based on financial analysis to maintain stable financial performance.